Legal Implications of Digital Platform Models: Regulatory Approaches to Consumer Protection, Data, and Competition for Start-up Sustainability - Marsal, Antonino Pedro; Hardyansah, Rommy (Metromedia, 2025)
This paper investigates the complex relationship between legal frameworks and the sustainability of digital platform business models, with a focus on application-driven start-ups in emerging digital economies. By employing a qualitative literature study and thematic synthesis, the research dissects how statutes addressing consumer protection, personal data management, and competition law affect the operational certainty and continuity of digital enterprises. Findings reveal that most legal systems are still evolving, struggling to reconcile the unique characteristics of digital commerce with outmoded legal paradigms and fragmented regulatory oversight. Inadequate harmonization, resource scarcity, and gaps in institutional capacity further exacerbate these issues, imposing substantial burdens on start-up compliance and inhibiting technological innovation. The research demonstrates that sustainable solutions require not only legislative renewal and harmonization but also active collaboration between stakeholders, ongoing capacity building, and adaptive regulatory innovation. Recommendations include modular reforms, increased emphasis on technology-driven oversight, stakeholder-inclusive policy processes, and development of regulatory sandboxes to bridge the gap between innovation and public interest. The outcomes highlight the necessity for flexible, knowledge-based, and principle-driven governance structures that support both entrepreneurial dynamism and societal protection in the rapidly shifting digital economy